Sentiment Analysis Using State of the Art Machine Learning Techniques - Balci, Salih; Demirci, Gozde Merve; Demirhan, Hilmi; Sarp, Salih (Springer International Publishing Ag, 2022)
Sentiment analysis is one of the essential and challenging tasks in the Artificial Intelligence field due to the complexity of the languages. Models that use rule-based and machine learning-based techniques have become popular. However, existing models have been under-performing in classifying irony, sarcasm, and subjectivity in the text. In this paper, we aim to deploy and evaluate the performances of the State-of-the-Art machine learning sentiment analysis techniques on a public IMDB dataset. The dataset includes many samples of irony and sarcasm. Long-short term memory (LSTM), bag of tricks (BoT), convolutional neural networks (CNN), and transformer-based models are developed and evaluated. In addition, we have examined the effect of hyper-parameters on the accuracy of the models.
9th Machine Intelligence and Digital Interaction Conference (MIDI) -- DEC 09-10, 2021 -- Warsaw, POLAND
Keywords: Sentiment analysis; Bag of tricks; Transformer; BERT; CNN